ANALISIS KEY SUCCESS FACTORS KEPEMIMPINAN DAN PERAN SITE MANAGER SEBAGAI PIMPINAN LEVEL MENENGAH DI PROYEK TOL CISUMDAWU - Gunawan, Muhammad Ihsan; Sakti, Wahyu Indra (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2024)
This research aims to analyze the role and duties of the site manager as a middle level leader on the Cisumdawu toll road project and analyze the key success factors of site manager leadership as a middle level leader on the Cisumdawu toll road project. There are two benefits to this research, theoretical benefits, to find out the key success factors for site manager leadership. Practical benefits can be a reference material for other agencies or parties to become effective leaders. Quantitative research method using literature study and questionnaire data collection techniques. The location of the research object is the Cileunyi–Sumedang–Dawuan (Cisumdawu) Toll Road Project. The results of the research show 10 key leadership factors for site managers as middle level leaders in projects. Abstrak Penelitian ini bertujuan untuk menganalisis peran dan tugas site manager sebagai pimpinan level menengah pada proyek tol Cisumdawu dan menganalisis key success factor kepemimpinan site manager sebagai pimpinan level menengah pada proyek tol Cisumdawu. Ada dua manfaat penelitian ini manfaat teoritis, untuk mengetahui key success factor kepemimpinan site manager. Manfaat praktis, dapat menjadi bahan acuan bagi instansi atau pihak lain untuk menjadi pemimpin yang efektif. Metode penelitian kuantitatif dengan teknik pengumpulan data studi literatur dan kuesioner. Lokasi objek penelitian yaitu di Proyek Jalan Tol Cileunyi–Sumedang–Dawuan (Cisumdawu). Hasil dari penelitian terdapat 10 faktor kunci kepemimpinan site manager sebagai pimpinan level menengah di proyek.